The RuIV=O-catalyzed sulfoxidation: a gated mechanism where O to S linkage isomerization switches between different efficiencies - Benet-Buchholz, Jordi; Comba, Peter; Llobet, Antoni; Roeser, Stephan; Vadivelu, Prabha; Wiesner, Sebastian (Dalton transactions, 2010)
Two Ru(IV)=O catalysts with either a pentadentate bispidine ligand L(1) or a bidentate pyrazolate L(2)/terpy L(3) combination of ligands have very different efficiencies as oxygen transfer catalysts for the selective oxidation of sulfides to sulfoxides: the [Ru(II)(L(1))(solvent)](2+)/iodosyl benzene system has an initial TOF of approx. 40 h(-1) and quantitative yield, with [Ru(II)(L(2))(L(3))(solvent)](+) the initial TOF is approx. 12 h(-1) with a maximum yield of approx. 60%. By experiment (cyclovoltametry) it is shown that there is S- to O-linkage isomerization of the Ru(II) sulfoxide product complex, and this may partially switch off the catalytic cycle for the L(2)/L(3)-based catalyst. It emerges that the reasons for the reduced efficiency in the case of the L(2)/L(3), in comparison with the L(1)-based catalyst, are a more efficient linkage isomerization, a more stable S-bonded, in comparison with the O-bonded, Ru(II)-based isomer, and inefficient ligand exchange in the product (hydrolysis produces the free sulfoxide and the Ru(II) precatalyst). These interpretations are qualitatively in good agreement with preliminary DFT-based data.
Im Titel ist "IV" hochgestellt
Gesehen am 12.01.2023